2016
DOI: 10.1111/jfb.13054
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of a whale shark Rhincodon typus aggregation in the Red Sea

Abstract: The presence of whale sharks Rhincodon typus were recorded around Shib Habil, a small, coastal reef off the Red Sea coast of Saudi Arabia, from 2010 to 2015. A total of 267 suitable photographs resulting in the identification of 136 individuals, were documented from 305 encounters. Sharks were divided evenly between the sexes with no evidence of temporal or spatial segregation. All individuals were immature based on size estimates and, for males, juvenile clasper morphology. Scars were reported for 57% of R. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 46 publications
4
37
0
Order By: Relevance
“…In Ningaloo Reef, Western Australia, Holmberg et al (2009) estimated whale sharks spent 33 days in the area using different methods. Contrastingly, at Utila Bay, Honduras and at an aggregation in Saudi Arabia's Red Sea, whale sharks spent c. 12 days in these areas, suggesting whale sharks are likely more transient there (Fox et al, 2013;Cochran et al, 2016). Residency patterns estimated through conventional mark-recapture techniques are a useful, noninvasive method for determining how whale sharks use certain sites.…”
Section: Discussionmentioning
confidence: 99%
“…In Ningaloo Reef, Western Australia, Holmberg et al (2009) estimated whale sharks spent 33 days in the area using different methods. Contrastingly, at Utila Bay, Honduras and at an aggregation in Saudi Arabia's Red Sea, whale sharks spent c. 12 days in these areas, suggesting whale sharks are likely more transient there (Fox et al, 2013;Cochran et al, 2016). Residency patterns estimated through conventional mark-recapture techniques are a useful, noninvasive method for determining how whale sharks use certain sites.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, it is one of the only areas from which immature whale sharks, of both sexes, and large mature females have been routinely recorded (Clark & Nelson, 1997; Eckert & Stewart, 2001; Ramírez-Macías et al, 2007; Ramírez-Macías, Vázquez-Haikin & Vázquez-Juárez, 2012; Ketchum, Galván-Magaña & Klimley, 2013; Cochran et al, 2016). Some of the few reported neonatal whale sharks have also been found in this region (Wolfson, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study demonstrate that whale sharks within the WCA represent an open population with significant emigration and re-immigration (incorporating permanent emigration), which is not surprising considering their large size and movement capabilities of this species [ 28 , 32 , 33 , 40 ]. Previous studies have shown open population models are the most appropriate for population estimates of whale sharks from photo-identification data [ 41 , 53 ] and the lack of asymptote in the discovery curve, as we observed, indicates that new animals are entering the region [ 28 , 29 ]. Given the vast available habitat for whale sharks in the WCA, it is entirely plausible that additional aggregation sites occur within the area that have not been identified by researchers or tourism.…”
Section: Discussionmentioning
confidence: 76%
“…The vast majority of whale shark data available is derived from juvenile male-dominated aggregation sites, with few exceptions [ 1 ]. Even the sexually integrated population in the Red Sea does not represent a reproductive population because the animals are immature [ 28 ]. This is also true for the entire WCA, which is dominated by males and 89% of the sampled individuals were smaller than size of maturity estimates (7.0–8.0 m) [ 5 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation